Implementation of the Independent Learning Curriculum and itsImplications for Improving Teacher Professionalism in Indonesia - Indrawati, Dwi; Timan, Agus (Proceedings Series of Educational Studies, 2025)
The implementation of the Independent Curriculum requires teachers to be more innovative, creative, and adaptable to the diverse needs of students. Teachers no longer act only as conveyors of material, but as facilitators who support competency-based and character-based learning. Teacher professionalism is a key element in the success of this curriculum, with a focus on improving pedagogical, technological, and soft skills such as critical thinking and collaboration skills. This study uses a qualitative descriptive method with a literature review approach. Data were obtained from various sources, including books, journals, and related documents that are relevant to the research topic. The results of the study show that although there are challenges in its implementation, such as limited technological infrastructure and teacher readiness, the government has provided support through training programs and improving teacher welfare. Overall, theimplementation of the Independent Curriculum has a positive impact on improving teacher professionalism in Indonesia and makes an important contribution to improving the quality of national education.